Predictors of Long-Time Survivors in Nonmetastatic Colorectal Signet Ring Cell Carcinoma: A Large Population-Based Study - Wuguang Zhang; Wenqian Gong; Changhai Wu; Mengting Li; Xiaolong Tu (Gastroenterology Research and Practice)
Background. Colorectal signet ring cell carcinoma (SRCC) is a rare and distinct subtype of colorectal cancer (CRC), with extremely poor prognosis and aggressive tumor biological behavior. In this study, we aimed to analyze the clinicopathological characteristics and to identify the independent predictors of long-time survivors (LTSs) of nonmetastatic colorectal SRCC. Methods. Patients diagnosed with nonmetastatic colorectal SRCC were extracted from the Surveillance, Epidemiology, and End Results (SEER) database. We compared and analyzed the clinicopathological characteristics between LTSs (patients survived over 5 years) and non-LTSs (patients survived of or less than 5 years). Afterwards, multivariate logistic regression analysis was used to identify independent predictors of LTSs, which were further used to construct a nomogram model to predict the probability of being LTSs. Results. We enrolled 2050 patients with nonmetastatic colorectal SRCC, consisting of 1441 non-LTSs and 609 LTSs. Multivariate logistic regression analysis revealed that race, marital status, tumor infiltration, lymph node involvement, and primary tumor treatment were independent predictors of LTSs. In addition, these five parameters were incorporated into a nomogram model to predict the probability of being LTSs. In terms of the model performance, the calibration curve revealed good agreement between observed and predicted probability of LTSs, and receiving operator characteristic curve showed acceptable discriminative capacity in the training and validation cohorts. Conclusion. Collectively, we analyzed and profiled the clinicopathological characteristics of LTSs in patients with nonmetastatic colorectal SRCC. Race, marital status, T stage, N stage, and primary tumor treatment were independent predictors of LTSs.